(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article provides an overview of the main characteristics of nosocomial infections. It provides a general discussion on how important healthcare is for the spread of infections, as well as on methods of their prevention and management. This exercise discusses methods for the assessment, management and prevention of nosocomial infections. It highlights how important the medical team is in evaluating, managing and improving the care of patients with this disease. Hospital-acquired infections are a serious health problem in developing countries. The rising incidence rate leads to longer hospital stays, higher psychological burdens, higher treatment costs and higher antibiotic resistance. VI is most often associated with gram-negative bacteria in the intestine. In addition, the most frequent VIS were in the intensive care unit. Postoperative infections were the most common type of infection. The results showed that there is a significant correlation between average age and different hospital wards. In addition, it was found that there is a significant correlation between gender and the hospital ward. All hospital staff should receive regular noise reduction training, especially in wards where invasive treatments are used.